Model testing capabilities for verification of floatover operations - Magee, A. (International Society of Offshore and Polar Engineers, 2014)
Investigations into the barge motions, mating load interfaces between the topside leg and jacket leg and mooring lines tensions for floatover installations are presented. Floatover installation means an operation of transferring the topside onto its fixed or floating substructure dependent mainly on the barge ballasting operation without the service of the lift crane vessel. This paper demonstrates the capabilities of floatover model test conducted in the wave basin of Universiti Teknologi PETRONAS. The instrumentation and model test procedure are described in detail. The paper presents comparisons between the calculations and experimental results for mutual verification. Copyright Â© 2014 by the International Society of Offshore and Polar Engineers (ISOPE).